2010
DOI: 10.1021/ja106588m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Catalytic Cyclohydroamination by Zirconium Salicyloxazoline Complexes

Abstract: The mechanism of hydroamination/cyclization of primary aminoalkenes by catalysts based on Cp*LZr(NMe(2))(2) (L = κ(2)-salicyloxazoline) is investigated in a range of kinetic, stoichiometric, and structural studies. The rate law is found to be d[substrate]/dt = k[catalyst](1)[substrate](0) for all catalysts and aminoalkenes studied. The overall rate is similar for formation of five- and six-membered rings, and a substantial KIE (k(H)/k(D)) is observed, indicating the involvement of N-H bond-breaking in a rate-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 91 publications
3
25
0
2
Order By: Relevance
“…An alternate explanation for the primary kinetic isotope effect and zero-order dependence on substrate concentration is reaction by a mechanism involving turnover-limiting formation of a metal imido intermediate. [73,74] Additional studies are clearly needed to delineate the relationships between the experimental data and mechanisms of hydroamination catalyzed by alkaline earth, group IV, and lanthanide complexes.…”
Section: Catalytic Reactions Involving Insertions Into the Metal-nitrmentioning
confidence: 99%
“…An alternate explanation for the primary kinetic isotope effect and zero-order dependence on substrate concentration is reaction by a mechanism involving turnover-limiting formation of a metal imido intermediate. [73,74] Additional studies are clearly needed to delineate the relationships between the experimental data and mechanisms of hydroamination catalyzed by alkaline earth, group IV, and lanthanide complexes.…”
Section: Catalytic Reactions Involving Insertions Into the Metal-nitrmentioning
confidence: 99%
“…Indeed, early computational work on a cyclopentadienyl system suggested that while the [2+2] cycloaddition step is energetically feasible, the subsequent protonolysis step for catalyst turnover is turnover-limiting [40,59]. More recently, Scott and coworkers [60] showed experimentally that proton transfer in the release of product and generation of the requisite zirconium imido complex can be turnover-limiting (Scheme 15.10). Previously reported bis(amidate)-and tethered-amidate-supported zirconium complexes can be used for alkene hydroamination catalysis, and all substrate scope and mechanistic investigations of these systems are consistent with the [2+2] cycloaddition mechanistic profile [61,62].…”
Section: Mechanistic Insightsmentioning
confidence: 99%
“…Anschließend schlugen Schafer und Mitarbeiter einen ähnlichen Übergangszustand für die Hydroaminierung primärer und sekundärer Aminoalkene vor, die durch Zirconium-Komplexe mit anhängendem Bis(ureat) katalysiert wurden. [73,74] Weitere Studien sind eindeutig erforderlich, um die Beziehungen zwischen den Versuchsdaten und den Mechanismen der Hydroaminierungen, die durch Erdalkali-, Gruppe-IV-und Lanthanoid-Komplexe katalysiert werden, zu beschreiben. [53,[58][59][60] Die Reaktionsordnung bezüglich dem Substrat in Verbindung mit Informationen über den Ruhezustand sowie die KIE-Werte deuten auf Parallelen zwischen diesen Systemen hin.…”
Section: Migratorische Insertionunclassified
“…Eine alternative Erklärung für den primären kinetischen Isotopeneffekt und die Abhängigkeit erster Ordnung von der Substratkonzentration ist eine Reaktion, deren Mechanismus die Bildung eines Metall-Imido-Intermediats als umsatzbestimmenden Schritt enthält. [73,74] Weitere Studien sind eindeutig erforderlich, um die Beziehungen zwischen den Versuchsdaten und den Mechanismen der Hydroaminierungen, die durch Erdalkali-, Gruppe-IV-und Lanthanoid-Komplexe katalysiert werden, zu beschreiben.…”
Section: Reaktionen Mit Migratorischer Insertion Von Olefinen In M-n-unclassified